2011
DOI: 10.1111/j.1469-8137.2011.03929.x
|View full text |Cite
|
Sign up to set email alerts
|

Rice DUR3 mediates high‐affinity urea transport and plays an effective role in improvement of urea acquisition and utilization when expressed in Arabidopsis

Abstract: Summary Despite the great agricultural and ecological importance of efficient use of urea‐containing nitrogen fertilizers by crops, molecular and physiological identities of urea transport in higher plants have been investigated only in Arabidopsis. We performed short‐time urea‐influx assays which have identified a low‐affinity and high‐affinity (Km of 7.55 μM) transport system for urea‐uptake by rice roots (Oryza sativa). A high‐affinity urea transporter OsDUR3 from rice was functionally characterized here f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 39 publications
8
69
1
Order By: Relevance
“…The region containing the other two substitutions was not covered by ESTs. However, the presence of asparagine (N) and histidine (H) instead of lysine (K) and glutamine (Q), respectively, was also found in the amino-acid sequence of rice OsDUR3 [19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region containing the other two substitutions was not covered by ESTs. However, the presence of asparagine (N) and histidine (H) instead of lysine (K) and glutamine (Q), respectively, was also found in the amino-acid sequence of rice OsDUR3 [19]. …”
Section: Resultsmentioning
confidence: 99%
“…AtDUR3 showed no significant homology to any other protein of Arabidopsis [13]. Similarly, in the rice genome, OsDUR3 is the only gene that has significant homology to AtDUR3 , suggesting that plant DUR3 proteins might represent a transporter subfamily consisting of only one member [18,19]. To date, in higher plants only Arabidopsis and rice DUR3 have been characterized at the molecular and physiological level [13,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence suggests that DUR3 is the main component of the high affinity transport system for urea acquisition in roots and the expression of DUR3 gene appears to be induced under N starvation. 12,37,38 Data reported in Arabidopsis and maize have revealed that the urea acquisition is induced by the presence in the external solution of the substrate itself. 8,39 In particular in maize roots, the high affinity transport system of urea appeared to be inducible by urea itself, retro-regulated and dependent on the external urea concentration and on the duration of root exposure to the N source.…”
Section: -15mentioning
confidence: 99%
“…For example, Gu et al (2013) observed an up-regulation of the two Zea mays (corn) ammonium transporter genes ZmAMT1;1a and ZmAMT1;3 when ammonium, but not nitrate, was resupplied after N starvation, indicating a substrate-specific regulation. Wang et al (2012) analysed expression of the high-affinity urea transporter gene OsDUR3 from rice ( Oryza sativa ) and found that it is generally up-regulated in roots during N depletion; in addition it can be specifically induced by the addition of urea, but not by ammonium, also indicating a substrate-specific regulation. In addition to effects on gene expression, Engelsberger and Schulze (2012) recently reported that N resupply leads to alterations in protein phosphorylation patterns within minutes after addition of N in the form of either nitrate or ammonium.…”
Section: Introductionmentioning
confidence: 99%